Xtation: um ambiente para execução e teste de aplicações interativas para o Middleware Ginga - Silva, Fernanda Paulinelli Rodrigues (2010)
Providing an infrastructure for the accomplishment of real tests in Applications for Interactive Digital TV (IDTV) involves the use of avant‐garde technologies and, consequently, it depends on a high investment in an infrastructure that simulates the operation of a Television Network. This investment is a technological barrier that restrains the knowledge dissemination in the development and test of IDTV programs. In order to overcome this problem, this work proposes the development of Xtation, an environment for execution and test of IDTV applications based on Ginga, the reference middleware of the Brazilian Digital Television System (SBTVD). Through a distributed architecture composed of a set of tools remotely controlled by a simple and intuitive application, the Xtation's main attraction is its low cost to allow for reliable testing of interactive applications by simulating a real IDTV environment.